Developing Children's Social Emotional: Women's Leadership Review - Moh. Anwar (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to analyze and understand women's leadership in building children's emotional-social intelligence in PAUD Aisyiyah Gilimanuk Jembrana Bali. The qualitative case study method is used in this investigation. The information was gathered through a combination of observation, interviews, and documentation. The data analysis was carried out circularly, beginning with data collection and progressing through data reduction, presentation, and conclusion. As a result of the findings; PAUD Aisyiyah is a female leader who is highly dedicated to creating a polite culture program to build children's emotional-social intelligence. Efforts to construct emotional-social intelligence are carried out properly through the following stages; reliable leadership for early childhood, educator for teachers and students, managerial and administrator, supervisor, innovator, and motivator. This research has implications for the importance of female leaders in building an excellent organizational culture, especially in creating emotional-social intelligence for children at school, through the involvement of all components.